THE IMPLEMENTATION OF NATIONAL SHARIA BOARD’S FATWA NUMBER 108 YEAR 2016 ABOUT SHARIA TOURISM ON HALAL TOURISM PRODUCTS - Hidayat, Muhammad Rifqi; Komarudin, Parman (AKADEMIKA: Jurnal Pemikiran Islam, 2019)
The fatwa of the National Sharia Board (DSN), specifically aimed to Islamic financial institutions (LKS), is always binding and must be adhered by Islamic financial institutions based on Undang-Undang Nomor 21 Tahun 2008 about Sharia Banking. But not in the DSN Fatwa Number 108 about sharia tourism, because there are not regulations of legislation in Indonesia that require sharia-related tourism elements to observe this fatwa. So, this research is carried out to analyze how sharia travels agencies Practice if reviewed by DSN fatwa. Data will be taken from PT. Rizma Tour & Travel which has halal tourism products, with a triangulation system through interviews, observation, and documents. The data used analyzed qualitatively using a juridical-sociological approach. The results of this research that PT. Rizma has implemented all the conditions required by the fatwa according to their needs on business basis, even though juridical it is not as ideal as what the DSN wants. Then needed a legal basis to raise the DSN fatwa of sharia tourism in order that must be implemented by businessmen, this is the technical instructions that contain the way of implementations and exceptions in application on the field.